Barley yellow dwarf virus transmission and feeding behaviour of Rhopalosiphum padi on Hordeum bulbosum clones. Issue 3 (5th February 2013) - Schliephake, E.; Habekuss, A.; Scholz, M.; Ordon, F.
Abstract A Hordeum bulbosum L. (Poaceae) clone A17 was identified, which showed complete resistance to Barley yellow dwarf virus (BYDV) and Cereal yellow dwarf virus (CYDV). It was not possible to infect plants of A17 with BYDV‐PAV, ‐MAV, or with CYDV‐RPV by the aphid vectors Rhopalosiphum padi (L.) or Sitobion avenae (Fabricius) (both Hemiptera: Aphididae). Plants of the A17 clone and of the BYDV‐susceptible H. bulbosum clone A21 revealed some resistance to R. padi compared to the susceptible winter barley cultivar Rubina [Hordeum vulgare L. (Poaceae)]. The development time to the imago was longer and the number of nymphs was reduced on both clones compared with cv. Rubina. The probing and feeding behaviour of R. padi on plants of the H. bulbosum clones was studied over 12 h and compared with that on plants of the barley cv. Rubina. Principal component analysis of the results of the feeding behaviour revealed a clear separation of the H. bulbosum genotypes from Rubina. On H. bulbosum the number of penetrations was higher but total feeding time was shorter. Significant differences were mainly found in the phloem feeding parameters for plants of both clones in comparison to Rubina, with the virus resistant A17 clone having the strongest effect and the susceptible A21 clone being intermediate. Most significant differences were found in parameters of the phloem salivation phase. On A17, an average of less than one (0.9) E1 phase per plant was observed (3.3 on A21 and 5.7 on Rubina) and its duration was reduced to less than 1 min (0.9 min) in comparison to 2.4 min on A21 and 5.7 min on Rubina. Also, the phloem feeding (E2) phase was clearly reduced on A17 plants with 0.5 E2 phases per test and a mean duration of 1.1 min in contrast with 2.9 and 3.5 E2 phases per test and 34.1 and 421.3 min for A21 and Rubina, respectively. These results point towards a phloem‐localized factor for aphid resistance in H. bulbosum, i.e., on A17 plants the phloem salivation time is too short for a successful infection by BYDV leading to vector resistance.